Enhanced Light-Driven Antimicrobial Activity of Cationic Poly(oxanorbornene)s by Phthalocyanine Incorporation into Polymer as Pendants - AKSU, MEHMET BURAK (WILEY-V C H VERLAG GMBH, 2020)
Amphiphilic poly(oxanorbornene)s are promising synthetic polymers that mimic the structural properties and antimicrobial functions of naturally occurring antimicrobial peptides. Here, poly(oxanorbornene)s bearing pendant zinc(II) phthalocyanine and triphenyl(ethyl) phosphonium functionalities are synthesized by ring-opening metathesis polymerization (ROMP). Fluorescence, singlet oxygen and triplet quantum yields of polymers are measured in dimethyl sulfoxide and aqueous medium. The singlet oxygen quantum yields of copolymers with the highest triphenyl and triethyl phosphonium content are found to be 0.29 and 0.41, respectively. Then, antimicrobial activities of polymers against Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus) are investigated under both dark and light conditions. Synergistic effect of zinc(II) phthalocyanine and phosphonium-containing poly(oxanorbornene) is observed that the conjugate possessing the most triphenyl phosphonium side chains has the highest activity under light against both gram-positive and gram-negative bacterial strains after 80 min irradiation, reducing the survival of E. coli or S. aureus by 99.9999%. Hemolytic concentrations of the copolymers are found between 8 and 512 mu g mL(-1). Scanning electron microscopy (SEM) proves that the bacteria membrane deforms after contacting with the biocidal polymer.
Keywords: macromolecular photosensitizers; PACT; phthalocyanine; poly(oxanorbornene); ROMP; singlet oxygen; PHOTODYNAMIC THERAPY; SINGLET OXYGEN; PHOTOPHYSICAL PROPERTIES; ZINC(II) PHTHALOCYANINE; SYNTHETIC MIMICS; ANTIBACTERIAL; ROMP; PHOTOOXIDATION; SUBSTITUENTS; AGGREGATION